Corporate social responsibility : financial inclusion in the ecuadorian private banking system - Acosta Palomeque, Galo Ramiro (2019)
Fil: Acosta Palomeque, Galo Ramiro. University of the Armed Forces ESPE. Department of Economic, Administrative and Trade Sciences; Ecuador.